Ecofeminism and Constitutional Morality: Reclaiming the Feminine Principle in Indian Environmental Jurisprudence - Makwana, Heena Nityanand (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
The Indian constitutional landscape is currently witnessing a paradigm shift where the rigid boundaries of lex scripta are being permeated by the fluid and urgent necessities of the Anthropocene. This research paper provides an exhaustive legal synopsis and jurisprudential analysis of the intersection between Ecofeminism, a critical theory linking the oppression of women with the domination of nature, and Constitutional Morality, a judicial doctrine prioritizing the substantive values of the Constitution over societal norms. In the Indian context, environmental jurisprudence has historically oscillated between utilitarian development models and rights-based conservation. However, the specific and gendered impacts of environmental collapse, which are borne disproportionately by women responsible for subsistence labor, have often remained on the periphery of constitutional analysis. This study argues that the doctrine of Constitutional Morality, as evolved by the Supreme Court of India, provides the necessary jurisprudential framework to operationalize ecofeminist ethics, bridging the gap between ancient Indian Knowledge Systems and modern legal theory. By tracing the genealogy of ecological thought from the Vedic concept of Rta to the landmark 2024 ruling in M.K. Ranjitsinh, this document proposes a Dalit Ecofeminist praxis. It argues that Constitutional Morality mandates the State to uphold the substantive guarantees of dignity and equality against majoritarian vox populi, thereby dismantling the patriarchal capitalist structures that facilitate both gender injustice and ecological destruction.